Unilateral Vocal Cord Paralysis of a Great Jewish Opera Singer - Duek, Irit (Rambam Maimonides Med J, 2018)
George London was one of the most compelling vocal artists of the early twentieth century. At the age of 47, the great bass-baritone retired from singing. It has been suggested that the premature ending of his operatic career was due to unilateral vocal cord palsy (UVCP). When London retired, the common belief was that this UVCP was caused by viral hepatitis, although there is no evidence to support such an etiology. London’s medical records eliminate the possible etiology of a neck neoplasm, and the long period of time between a heart attack he experienced and his diagnosis of UVCP makes a cardiovascular etiology an unlikely causative factor. London’s relatively young age, the diagnosis of laryngitis prior to his UVCP, and the course of his disease indicate that the underlying cause of the termination of his singing career was post-viral neuropathy. This paper describes the clinical evidence related to London’s vocal cord function and explores the possible causes for his UVCP, which apparently led to his early retirement.